Investigation of PZT-5H and PZT-8 type piezoelectric effect on cycling stability on Si-MWCNT containing anode materials - Dogrusoz, Mehbare; Demirkan, M. Taha; DEMIR-CAKAN, Rezan (Tubitak Scientific & Technological Research Council Turkey, 2021)
Silicon (Si) containing materials cannot be used in commercial lithium ion batteries due to the mechanical stress problem triggered by volume expansion during cycling. The high-volume change causes mechanical instability of Si anode materials during charging/discharging, resulting fast capacity fading. It is thought that piezoelectric materials can be a solution for the volume expansion problem because of their ability to generate electric field when pressure is applied on them. For this purpose, PZT-8 and PZT-5H type piezoelectric materials were mixed with silicon and multiwalled carbon nanotube (MWCNT) to obtain anode composites and tested electrochemically versus lithium metal. The piezoelectiric effect on the electrochemical activity of these anodes is investigated by preparing the anode composite without any piezoelectric material additive (Sample #3). At the end of the 50 charge/discharge cycles, the capacities reached 420 mAh/g, 300 mAh/g and 100 mAh/g for PZT-8-added, PZT-5H-added and no-PZT samples, respectively. These results showed that PZT addition improves capacity performance of Si-MWCNT anodes. Additionally, the obtained anode composites were characterized with X-ray diffraction and scanning electron microscopy.
Investigation of PZT-5H and PZT-8 type piezoelectric effect on cycling stability on SiMWCNT containing anode materials
Keywords: Silicon anode; lithium ion battery; piezoelectric additives